Breast cancer prediction using different machine learning models - Khandker Al- Muhaimin; Tahsan Mahmud; Sudeepta Acharya; Ashiqul Islam (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.